Biosolids Effects in Chihuahuan Desert Rangelands: A Ten-Year Study - David B. Wester; Ronald E. Sosebee; Richard E. Zartman; Ernest B. Fish; J. Carlos Villalobos; Ricardo Mata-Gonzalez; Pedro Jurado; Corey A. Moffet (Applied and Environmental Soil Science)
Arid and semiarid rangelands are suitable for responsible biosolids application. Topical application is critical to avoid soil and vegetation disturbance. Surface-applied biosolids have long-lasting effects in these ecosystems. We conducted a 10-year research program investigating effects of biosolids applied at rates from 0 to 90 dry Mg ha−1 on soil water infiltration; runoff and leachate water quality; soil erosion; forage production and quality; seedling establishment; plant physiological responses; nitrogen dynamics; biosolids decomposition; and grazing animal behavior and management. Biosolids increased soil water infiltration and reduced erosion. Effects on soil water quality were observed only at the highest application rates. Biosolids increased soil nitrate-nitrogen. Biosolids increased forage production and improved forage quality. Biosolids increased leaf area of grasses; photosynthetic rates were not necessarily increased by biosolids. Biosolids effects on plant establishment are expected only under moderately favorable conditions. Over an 82-mo exposure period, total organic carbon, nitrogen, and total and available phosphorus decreased and inorganic matter increased. Grazing animals spent more time grazing, ruminating, and resting in biosolids-treated areas; positive effects on average daily gain were observed during periods of higher rainfall. Our results suggest that annual biosolids application rates of up to 18 Mg ha−1 are appropriate for desert rangelands.